Automated Quantification of DNA Aneuploidy by Image Cytometry as an Adjunct for the Cytologic Diagnosis of Malignant Effusion - Zhilan Meng; Jie Shi; Chenyan Zhu; Jiangang Gu; Chen Zhou (Analytical Cellular Pathology)
DNA aneuploidy is a cancer biomarker, which may have a potential diagnostic value in body effusion specimen. DNA aneuploidy is determined by measuring the DNA content of tested cells and comparing them with diploid cells (2c). In order to assess the value of automated DNA image cytometry (DNA-ICM) in the cytologic diagnosis of effusion, we measured DNA ploidy using an automated DNA-ICM analysis system in 126 consecutive effusion specimens and followed the cases for histologic diagnosis. Half of each effusion specimen was used to prepare cytologic smears for conventional cytologic diagnosis, while the other half was used to prepare a monolayer slide stained by Feulgen stain for automated ICM. By using Youden index, we found that 4 cells exceeding 2.5c is the optimal cut off value for aneuploidy, which has a sensitivity of 88.3% and specificity of 100% for diagnosis of malignant effusion. We also found that the DNA aneuploidy thresholds used for other types of cytologic specimens cannot be used in the diagnosis of effusion specimens. Our study demonstrated that automated DNA image cytometry is a simple, practical and cost-effective method for adjunct diagnosis of malignant effusion.